Comprehensive determination of transcription start sites derived from all RNA polymerases using ReCappable-seq - Yan, Bo; Tzertzinis, George; Schildkraut, Ira; Ettwiller, Laurence

(untitled) (Genome Research, 2022)
Determination of eukaryotic transcription start sites (TSSs) has been based on methods that require the cap structure at the 5′ end of transcripts derived from Pol II RNA polymerase. Consequently, these methods do not reveal TSSs derived from the other RNA polymerases that also play critical roles in various cell functions. To address this limitation, we developed ReCappable-seq, which comprehensively identifies TSS for both Pol II and non–Pol II transcripts at single-nucleotide resolution. The method relies on specific enzymatic exchange of 5′ m7G caps and 5′ triphosphates with a selectable tag. When applied to human transcriptomes, ReCappable-seq identifies Pol II TSSs that are in agreement with orthogonal methods such as CAGE. Additionally, ReCappable-seq reveals a rich landscape of TSSs associated with Pol III transcripts that have not previously been amenable to study at genome-wide scale. Novel TSS from non–Pol II transcription can be located in the nuclear and mitochondrial genomes. ReCappable-seq interrogates the regulatory landscape of coding and noncoding RNA concurrently and enables the classification of epigenetic profiles associated with Pol II and non–Pol II TSS.